Identifikasi Pola Pemanfaatan Media Sosial Siswa Sekolah Dasar Islam Terpadu Al-Kautsar - Rusli, Muhammad; Samosir, Ridha Sefina (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
The utilization of social media is now reaching up to elementary school students including elementary Al-Kautsar. Lots of social media that is currently used include facebook, twitter, path and linkid. One of the factors driving the utilization of social media is the development and sophistication of todays technology. Social media applications can easily be planted on any smart mobile phone technology. Biggest driving factor is the sophistication, ease in use of social media, Ease Adding Friends/Community, Trend Following, Needs School, Most of the students own memamfaatkan social media and most have more than one social media, social media used are Facebook, Twitter, Instagram, Line, and Path. The utilization of social media for positive activities and its use was not in vain. The students mostly do not accept friend requests from strangers. This research use Force Field Analysis.